(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
Problem. The difficult economic situation in Ukraine has become an incentive for the priority development of domestic tourism. Therefore, the training of qualified specialists in the field of tourism, possessing theoretical knowledge, research skills and methods of tourism and local lore work, has acquired great importance. The purpose of the study. The purpose of our article is to show the possibilities of route practices from the point of view of the possibilities of forming research skills of different groups in future tourism specialists and in future teachers of geography, to reveal the differences and commonality in this matter for the two indicated categories. Presentation of the main material. We are convinced that route practice is an important component of the professional training of future specialists in the field of tourism and future teachers of geography. Practices of this kind ensure the consolidation of knowledge, skills and abilities of future professional activity, which students acquire during classroom studies. We consider the concept of "research skills" as a set of intellectual and practical actions that ensure the ability of a person to independently observe, generalize, analyze processes and phenomena of reality, to acquire new knowledge and use it in accordance with the set goal of research or professional activity. We have reduced all the variety of research skills necessary for future specialists to such five groups: operational, organizational, communicative, practical and cartographic. Among the variety of training practices for future specialists, a special place is occupied by a comprehensive practice in socio-economic geography and practice in active tourism. Each of them has the ability to form research skills. Traditionally, each of these practices has a preparatory, route and reporting stage. In addition, it is envisaged to carry out an individual study by each student on the topic of educational practice. The results of our research have confirmed that the route practice has all the possibilities for the formation of research skills of future specialists. However, there are certain differences in the selection of excursion objects and topics of individual assignments for each of these categories of students.